2016
DOI: 10.1136/bjophthalmol-2016-308754
|View full text |Cite
|
Sign up to set email alerts
|

The role of specific visual subfields in collisions with oncoming cars during simulated driving in patients with advanced glaucoma

Abstract: Background/aimsTo assess the role of specific visual subfields in collisions with oncoming cars during simulated driving in patients with advanced glaucoma.MethodsNormal subjects and patients with glaucoma with mean deviation <–12 dB in both eyes (Humphrey Field Analyzer 24-2 SITA-S program) used a driving simulator (DS; Honda Motor, Tokyo). Two scenarios in which oncoming cars turned right crossing the driver's path were chosen. We compared the binocular integrated visual field (IVF) in the patients who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
1
19
2
Order By: Relevance
“…A DS system (HONDA Safety Navi ‘glaucoma edition 2’, Honda Motor Co., Tokyo) was used for which details have been previously reported [ 2 3 ]. The simulation used a semi-automatically-controlled speed; subjects only had to brake in case of a vehicle suddenly appearing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A DS system (HONDA Safety Navi ‘glaucoma edition 2’, Honda Motor Co., Tokyo) was used for which details have been previously reported [ 2 3 ]. The simulation used a semi-automatically-controlled speed; subjects only had to brake in case of a vehicle suddenly appearing.…”
Section: Methodsmentioning
confidence: 99%
“…However, VF impairment can be artificially created by having subjects wear pinhole (PH) glasses. Comparison of involvement in MVAs during DS tests [ 3 ] between the same subjects with and without PH glasses would allow investigation of the effects of VF impairment, while adjusting for all traffic-, automobile- and subject-related conditions other than VF impairment. It is important to note that the PH of the same aperture can create a different level of VF constriction between individuals ( Fig 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a myriad of studies has reported the difficulties-e.g. driving within lane positions [14], coping with the sudden appearance of a pedestrian or vehicle [2,[15][16], an oncoming vehicle turned right crossing the driver's path at intersection [17], immediate reaction to divided attention [18], or obstacle avoidance [18][19][20][21]. The difficulty due to visual field defects is closely related to a driver's hazard perception; thus it is reported as one of the causes of traffic accidents [12,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the current study is to examine the effects of compensatory behaviour of drivers under visual field defects on avoiding unexpected traffic hazards during simulated driving. The main hazardous events were designed in accordance with the previous findings that patients with visual field defects have difficulty in avoiding the sudden appearance of a pedestrian or other vehicle from the sides [2,16,38], and that pedestrian collision is one of the most frequent types of traffic accidents [45]. We hypothesised that performing frequent head movements leads to a certain level of driving performance-i.e.…”
Section: Introductionmentioning
confidence: 99%